PENGEMBANGAN BUSINESS INTELLIGENCE BAGI PERKEMBANGAN BISNIS PERUSAHAAN - Miranda, Eka (Bina Nusantara University, 2008)
This article discusses the Business Intelligence and its role to improve the company’s competitive advantage through the utilization of various data, information and knowledge held by the company as a raw material in the decision making process. This article also explains the elements of Business Intelligence applications, Business Intelligence Environment, integrating BI into the enterprise and the challenges faced by organizations in giving effect to Business Intelligence.Keywords: Business Intelligence, business decision